2017
DOI: 10.1080/02602938.2017.1417974
|View full text |Cite
|
Sign up to set email alerts
|

A review of the characteristics of intermediate assessment and their relationship with student grades

Abstract: a iclon, leiden university graduate school of teaching, leiden university, leiden, the netherlands; b institute of Psychology, leiden university, leiden, the netherlands ABSTRACT In-course assessment, such as midterms, quizzes or presentations, is often an integral part of higher education courses. These so-called intermediate assessments influence students' final grades. The current review investigates which characteristics of intermediate assessment relate to these grades. In total, 88 articles were reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 96 publications
0
10
0
1
Order By: Relevance
“…The authors emphasize the need for large-scale studies that can analyze and validate the most efficient assessment tools for collaborative work. Day, van Blankensteina, Westenbergb and Admiraal [18] also analyzed the perceptions of students and teachers but they focused on the middle assessment. The authors found that both teachers and students have a positive opinion on the middle assessment.…”
Section: Assessment Methods In Higher Education Institutionsmentioning
confidence: 99%
“…The authors emphasize the need for large-scale studies that can analyze and validate the most efficient assessment tools for collaborative work. Day, van Blankensteina, Westenbergb and Admiraal [18] also analyzed the perceptions of students and teachers but they focused on the middle assessment. The authors found that both teachers and students have a positive opinion on the middle assessment.…”
Section: Assessment Methods In Higher Education Institutionsmentioning
confidence: 99%
“…The non-CA modules have two assignments and CA assessments can go up to 10 assignments. In a review of CA in higher education, Day et al (2018b) also found that the frequency of assessments differ. It is also typical in certain cases that learning activities within a module could be planned, say, for each week of the teaching period.…”
Section: Assignment Due Datementioning
confidence: 99%
“…CA helps reduce the negative effects of highstakes once-off examinations (rote memorization, cramming, and high anxiety) and helps to promote student learning (De Lisle, 2015;Holmes, 2018). The application of CA in higher education spans different disciplines (Rezigalla et al, 2017;Day et al, 2018c;Nayak et al, 2020;Zhan, 2020) and various pedagogic approaches (Day et al, 2018b;Llamas-Nistal et al, 2019;Chong et al, 2020). CA has also been shown to work in traditional contexts as well as through using online and interactive Information and Communications Technology (ICT) systems (González-Campos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, teachers reported what their ideal intermediate assessment would be, focusing on a 'perfect world' without practical constraints. Finally, the interviewer presented a hand-out with a short overview of intermediate assessment in the literature (preliminary results from a literature review by Day et al 2017b). Using the information on this hand-out, teachers further reflected on their ideas for ideal assessment.…”
Section: Interviewsmentioning
confidence: 99%